Analysis of Drug Management at Tegal City Pharmaceutical Installation - Al Yaqut, Muhammad Arto; Satibi, Satibi; Iswandi, Iswandi (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Medicine is one of the most essential elements in health service efforts. Good drug management will affect the availability of drugs and improve the degree of health in the community.Objectives: This study aims to determine the effectiveness and efficiency of drug management at the Tegal City Pharmaceutical Installation in 2021 related to compliance with the Indonesian Ministry of Health and WHO indicators.Methods: This research is descriptive research with a quantitative approach. Data was taken retrospectively through document tracing and supplemented with qualitative data through interviews to deepen findings in the field. Data obtained and the results of interviews with the Head of Installation and pharmaceutical personnel, totaling five respondents, will then be compared with standard indicators from the Indonesian Ministry of Health and WHO. Data analysis in this study used indicators of selection, procurement, distribution, and use of drugs. The values of the indicators that have been obtained are subsequently compared with the existing standard values.Results: The results of drug management research at the Tegal City Pharmaceutical Installation are at the selection stage of proposing drugs to Fornas. The procurement stage of drug suitability with Fornas is 96.4%, the fund allocation percentage is 92%, and the planning accuracy is 95.7%. The distribution stage of the level of drug availability 12-18 is 13.92 months, the accuracy of the number of distributions to the Puskesmas is 100%, the percentage of drugs experiencing empty stock, dead stock, and overstock is 0%, the percentage of damaged and expired drugs is 0%. The use stage of drug items per prescription is 3.5 drug items, the percentage of antibiotic use in non-specific patients is 30.7%, the percentage of non-pneumonia Acute Respiratory Infections (ARI) antibiotic use is 34.2%, and myalgia injection use is 0%.Conclusion: The conclusion of drug management at the selection, procurement, distribution, and use stages in 2021 carried out at the Tegal City Pharmaceutical Installation has yet to follow standards. Of the 14 indicators studied, only 8 follow the standard, and 6 other indicators still need compliance to evaluation.